2013
DOI: 10.4103/0970-9290.123369
|View full text |Cite
|
Sign up to set email alerts
|

An insight into dentin desensitizing agents - In vivo study

Abstract: Propolis proves to be a good natural and nontoxic option for treatment of dentin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…3,4,5 DH is an uncomfortable condition that affects function and quality of life. 6 The Oral Health-Related Quality of Life (OHRQoL) is the patient's own perception of how the state of the mouth impacts upon his or her quality psychometric properties of the adapted instrument in order to demonstrate the measurement properties needed for the intended application, such as reliability and validity. 14 Therefore, the aim of the present study was to adapt and validate the DHEQ-15 for use in the Brazilian-Portuguese language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,5 DH is an uncomfortable condition that affects function and quality of life. 6 The Oral Health-Related Quality of Life (OHRQoL) is the patient's own perception of how the state of the mouth impacts upon his or her quality psychometric properties of the adapted instrument in order to demonstrate the measurement properties needed for the intended application, such as reliability and validity. 14 Therefore, the aim of the present study was to adapt and validate the DHEQ-15 for use in the Brazilian-Portuguese language.…”
Section: Introductionmentioning
confidence: 99%
“…Todos itens devem ser respondidos em uma escala Likert de 7 pontos com as opções e os escores: concordo muito 7, concordo (6), concordo um pouco (5), nem concordo nem discordo (4), discordo um pouco (3), discordo (2) ou discordo muito (1).…”
unclassified
“…Hydroxyapatite is widely used as a coating of metallic implants for bones in order to improve and accelerate the process of osseointegration [14, 15]. Hydroxyapatite powder plays an important role in dentistry (e.g., in the treatment of dental pulp and dentine hypersensitivity) and is associated with the exposure of dentinal tubules [16, 17]. Hydroxyapatite, present in toothpastes and dental gels, reduces the deposition of accretions on teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The search for a natural desensitizing agent with long lasting effects has led to the observation that Propolis had promising effects on dentin hypersensitivity (6,12) . Also, it was observed that propolis has an anti-inflammatory action; it stimulates reparative dentin formation which would be able to reduce dentin permeability.…”
Section: Discussionmentioning
confidence: 99%
“…0.200 grams of propolis powder was prepared into a paste through mixing with 0.2 ml of Ethyl Alcohol (70%). The paste was freshly prepared just prior to its use (12) .…”
Section: Preparation Of Propolis Extract Pastementioning
confidence: 99%